Evaluation of a method for determining binaural sensitivity to temporal fine structure (TFS-AF test) for older listeners with normal and impaired low-frequency hearing - Füllgrabe, Christian; Moore, Brian C.J. (Sage, 2017)
The ability to process binaural temporal fine structure (TFS) information was assessed using the TFS-AF test (where AF stands for adaptive frequency) for 26 listeners aged 60 years or more with normal or elevated low-frequency audiometric thresholds. The test estimates the highest frequency at which a fixed interaural phase difference (IPD) of ϕ (varied here between 30° and 180°) can be discriminated from an IPD of 0°, with higher thresholds indicating better performance. A sensation level of 30 dB was used. All listeners were able to perform the task reliably, giving thresholds well above the lowest allowed frequency of 30 Hz. The duration of a run averaged 5 min. Repeated testing of the normal-hearing listeners showed no significant practice effects. Thresholds varied markedly across listeners, but their ranking was fairly consistent across values of ϕ. Thresholds decreased (worsened) with decreasing ϕ and were lower than for a group of young listeners tested in an earlier study. There were weak to moderate, negative correlations between TFS-AF thresholds and audiometric thresholds at low frequencies (125–1000 Hz) but not at high frequencies (4000–8000 Hz). In conclusion, the TFS-AF test yielded a graded measure of binaural TFS sensitivity for all listeners. This contrasts with the TFS-LF (low-frequency) test, which measures the smallest detectable shift in IPD for a fixed frequency. The absence of practice effects and a reasonably short administration time make the TFS-AF test a good candidate for the assessment of sensitivity to changes in binaural TFS for older listeners without or with hearing loss.